Olympic anti-doping laboratory: the analytical technological road from 2016 Rio de Janeiro to 2021 Tokyo - Saad, K.; Salama, S.; Horvatovich, P.; Maadheed, M. A.; Georgakopoulos, C. (Bioanalysis, 2020)
The summer Olympic Games is the major mega sports event since the first modern era Olympiad, held in Athens, Greece in 1896. International Olympic Committee (IOC) has the responsibility of the organization of the summer and winter Games ensuring the broadcast in all corners of earth. The World Anti-Doping Agency (WADA) is the responsible organization of the fight against doping in sports. IOC and WADA support the event's country WADA Accredited Laboratory to incorporate the maximum of the new analytical technologies to become applicable during the event's antidoping testing. The current study reviewed the last 5 years progresses of the antidoping system with emphasis on the laboratory field.